Quality of life is maintained with ixazomib maintenance in post-transplant newly diagnosed multiple myeloma: The TOURMALINE-MM3 trial - Schjesvold, Fredrik; Goldschmidt, Hartmut; Maisnar, Vladimir; Spicka, Ivan; Abildgaard, Neils; Rowlings, Philip; Cain, Lauren; Romanus, Dorothy; Suryanarayan, Kaveri; Rajkumar, Vincent; Odom, Dawn; Gnanasakthy, Ari; et al. (European journal of haematology, 2020)
OBJECTIVES: Health-related quality of life (HRQoL) is particularly important during maintenance therapy (MT) in newly diagnosed multiple myeloma post-transplant, when disease symptoms are limited. METHODS: We assessed HRQoL in patients randomised to 26 cycles of MT (ixazomib vs placebo) in TOURMALINE-MM3 (NCT02181413). RESULTS: The characteristics at study entry were well-balanced between ixazomib (n = 386) and placebo (n = 251) arms. At study entry, EORTC QLQ-C30 and MY20 scores were high for functional scales and low for symptom scales and were comparable with those of the general population. Changes in subscale scores across intervals, analysed over 30 four-week intervals using a linear mixed-effects model, were generally small and similar between arms for the EORTC QLQ-C30 Global Health Status/QoL, Physical Functioning, and Pain subscales and EORTC QLQ-MY20 Disease Symptoms subscale and Peripheral Neuropathy item. EORTC QLQ-C30 Nausea/Vomiting and Diarrhoea subscales were consistently worse for ixazomib than for placebo, in line with the ixazomib toxicity profile. Even when least-squares mean differences between arms were statistically significant, none reached the established minimal important clinical difference of 10 in multiple myeloma. CONCLUSIONS: In addition to improvement in progression-free survival with ixazomib, HRQoL was maintained in both arms. Active treatment with ixazomib did not have an adverse impact on HRQoL.
Keywords: hodnocení výsledků péče pacientem; Medication Adherence; kombinovaná terapie; transplantace hematopoetických kmenových buněk; Humans; lidé středního věku; Quality of Life; ixazomib; Hematopoietic Stem Cell Transplantation; Multiple Myeloma; sloučeniny boru; maintenance; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; udržovací chemoterapie; Antineoplastic Agents; výsledek terapie; Glycine; senioři; glycin; lidé; placebo-controlled; HRQoL; kvalita života; Maintenance Chemotherapy; mnohočetný myelom; Adult; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Antineoplastic Combined Chemotherapy Protocols; Boron Compounds; TOURMALINE-MM3; protinádorové látky; Combined Modality Therapy; mužské pohlaví; adherence k farmakoterapii; Patient Reported Outcome Measures